PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP HASIL BELAJAR BIOLOGI SISWA PADA MATERI POKOK BAHASAN VIRUS DIKELAS X MAN RANTAU PRAPAT - Desy Putriyani Harahap; Martina Restuati; Hardiansyah Hardiansyah (Jurnal Pelita Pendidikan, 2017)
This study aims to determine the effect of using a Problem based learning outcomes ofstudents at material virus in class X MAN Rantauprapat school year 2016/2017. This research is anexperimental study using as a tool. to obtain serearch data. The population in this study were allstudents of class X MAN Rantauprapat 2016/2017 school year. 7 class consisting of the number ofstudents 240 people. While the study sample is take in purposive sampling of 2 classes. Where classX2used as a control class with lecture learning methods with the number of students 40 people. Andclass X4used as the experimental class using the problem based learning of students 40 people. sonumber of sample in the study of 80 people. Based on the analysis of research data, reflecting theinfluenca of the learning autcomes and higer order thingking skills of students between classes withclass control experiments. Where the average value of the post-test results of on experimental classof student learning is at 79,12 and while the average value of the control class learning outcomes isat 74,87. The influence of problem based learning outcomes proven through hypothesis testingusing the f test with a significance level of α = 0.05, where F count > F ( 4,37 > 3,96), Which meansthat in this study HO is rejected at once accept Ha. Thus it can be concluded that there is influenceproblem based learning outocomes of studentsin the material virus in class X MAN Rantauprapatschool year 2016/2017.Keyword : Learning Outcomes, Problem Based Learning